Factors: Responsible for McDonald's Performance - Abhishek Rajawat; Daisy Mui Hung Kee; Muhammad Zulhilmi Bin Abdul Malik; Muqlis Alhayul Qayumm Bin Mohamed Yassin; Mai Shazatul Inaz Binti A. Shaffie; Maizatul Husna Binti Fuaat; Noof AlDosari; Maria Elisabeth Jessica Santoso (Journal of the Community Development in Asia (JCDA), 2020)
In the fast-food industry, MacDonald’s is a pioneer. It has more than 35,000 restaurants across the globe in 121 countries. McDonald's serves a variety of fast foods. For the average income customer, most of the item is priced so it could be a staple product. KFC, SUBWAY, IN&OUT, BURGER KING is one of the most prominent rivals in the country. The business strategies which are used by Macdonald’s in accordance with the market are different as it is following different strategy in Malaysia and different strategy in India. Comprehensive research is being carried out on how MacDonald is achieving tremendous success through its franchising model and factors that lead MacDonald's tremendously in the fast-food industry.